"Hearts, Hands and Heads": Exploring the Relationship Between Disengagement and Deradicalization Through Counter Violent Extremism Project Implementation in Indonesia - Brailey, Malcolm; Ismail, Noor Huda; Amir, Iwan (Muslim Politics Review, 2023)
Terrorism experts continue to debate how and why people become radicalised and commit violence. Significantly less emphasis and coherence of thought has been deployed to understand those processes in reverse. From the perspective of counterterrorism practitioners within both government and civil society, the question has tended to bifurcate around two contrasting conceptual approaches: should the focus be on ‘deradicalization’ (an internal or philosophical outcome seeking change in beliefs, values and attitudes) or ‘disengagement’ (a social or temporal outcome seeking change in behaviours away from violence)? This article seeks to contribute to the debate about how disengagement functions and stands as a practical and effective counterterrorism methodology, and is based on detailed analysis of field work and project implementation in Indonesia. This article and the methodologies implemented and tested are grounded in previous research on disengagement of Indonesian jihadists and countering violent extremism (CVE) projects conducted by several of the authors over many years, and extends and codifies the findings of a valuable body of earlier academic literature. The authors argue that a disengagement process grounded in the social methodology of personal mentoring (defined infra this paper by a process we have called ‘Hearts, Hands and Heads’) can achieve a measurable and meaningful change in how individuals withdraw from violent extremist networks. This article will further show why disengagement programs in Indonesia should prioritise targeting specific at-risk groups, including returned foreign fighters, who have been known to conduct terrorist activities in Indonesia as well as advocate for their cause and recruit more effectively than those that have never been to Syria or other conflict zones. With the proper implementation, disengagement can be an effective preventive tool in Indonesia in addition to preparing the groundwork for later, more formal deradicalization processes and programs.